EDUKASI PARENTING ISLAMI BERBASIS VIDEO HOME EDUCATION UNTUK MENINGKATKAN PERKEMBANGAN KOGNITIF ANAK DI DESA - Uswatun Hasanah Usnur; Sutrisni Sutrisni; Laila Darma Sari; Ridha Sakinah; Elvida Hanum (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Early childhood cognitive development is a fundamental aspect that determines learning success in later stages, where parental stimulation is a key factor. This community service project aims to examine the implementation of Islamic parenting education based on home education videos in improving children's cognitive development in Perbahingan Village, Serdang Bedagai Regency. Using a descriptive qualitative approach, the research subjects involved parents and early childhood children through observation, in-depth interviews, and documentation techniques. Education was provided through home education videos that integrate the values ​​of the Qur'an and Hadith with practical guidance on cognitive stimulation. The results of the activity indicate that the use of video media is highly effective due to its flexible nature, easy access, and appropriateness to rural communities. There was a significant increase in parents' understanding of Islamic parenting patterns and the intensity of their involvement in accompanying their children's learning at home. Positive impacts were also seen on children's cognitive aspects, particularly in the ability to recognize basic concepts, strengthen memory, think logically, and solve simple problems. Thus, Islamic parenting based on home education videos is an applicable alternative strategy for optimizing children's intellectual potential in line with spiritual values. The integration of digital technology in family education has proven to be able to bridge the limited access to information for parents in rural areas in a sustainable manner. ABSTRAK Perkembangan kognitif anak usia dini merupakan aspek fundamental yang menentukan keberhasilan belajar pada tahap selanjutnya, di mana stimulasi orang tua menjadi faktor kunci. Pengabdian masyarakat ini bertujuan untuk mengkaji implementasi edukasi parenting Islami berbasis video home education dalam meningkatkan perkembangan kognitif anak di Desa Perbahingan, Kabupaten Serdang Bedagai. Menggunakan pendekatan kualitatif deskriptif, subjek penelitian melibatkan orang tua dan anak usia dini melalui teknik observasi, wawancara mendalam, dan dokumentasi. Edukasi diberikan melalui media video home education yang mengintegrasikan nilai-nilai Al-Qur’an dan Hadis dengan panduan praktis stimulasi kognitif. Hasil kegiatan menunjukkan bahwa penggunaan media video sangat efektif karena sifatnya yang fleksibel, mudah diakses, dan sesuai dengan kondisi masyarakat pedesaan. Terjadi peningkatan signifikan pada pemahaman orang tua mengenai pola asuh Islami serta intensitas keterlibatan mereka dalam mendampingi anak belajar di rumah. Dampak positif juga terlihat pada aspek kognitif anak, khususnya dalam kemampuan mengenal konsep dasar, penguatan daya ingat, berpikir logis, dan pemecahan masalah sederhana. Dengan demikian, parenting Islami berbasis video home education menjadi strategi alternatif yang aplikatif untuk mengoptimalkan potensi intelektual anak yang selaras dengan nilai spiritual. Integrasi teknologi digital dalam pendidikan keluarga terbukti mampu menjembatani keterbatasan akses informasi bagi orang tua di wilayah pedesaan secara berkelanjutan.